On the importance of non-linear relationships between landscape patterns and the sustainable provision of ecosystem services - Grêt-Regamey, Adrienne; Lautenbach, Sven; Schlup, Barbara (Landscape ecology, 2014)
Marginal land use changes can abruptly result in non-marginal and irreversible changes in ecosystem functioning and the economic values that the ecosystem generates. This challenges the traditional ecosystem services (ESS) mapping approach, which has often made the assumption that ESS can be mapped uniquely to land use and land cover data. Using a functional fragmentation measure, we show how landscape pattern changes might lead to changes in the delivery of ESS. We map changes in ESS of dry calcareous grasslands under different land use change scenarios in a case study region in Switzerland. We selected three ESS known to be related to species diversity including carbon sequestration and pollination as regulating values and recreational experience as cultural value, and compared them to the value of two production services including food and timber production. Results show that the current unceasing fragmentation is particularly critical for the value of ESS provided by species-rich habitats. The article concludes that assessing landscape patterns is key for maintaining valuable ESS in the face of human use and fluctuating environment.
First online: 10 November 2013
Gesehen am 06.12.2018